The practice of fiscal federalism : comparative perspectives - Kincaid, John, 1946-; Shah, Anwar (Global dialogue on federalism, 2007)
Contributors provide a fascinating account of how federal countries are confronting the traditional challenges of conflicts over division of fiscal powers while also coping with emerging challenges of globalization and citizen empowerment arising from the information revolution. They analyze how relationships and roles in different orders of government are being reshaped and show how local solutions inspired by global principles help strengthen government accountability and improve the quality of life for citizens.